Penilaian Tingkat Kesehatan Keuangan Perusahaan Berdasarkan SK Menteri No. KEP-100/MBU/2002 (Studi Kasus PT Jasa Marga (Persero) Tbk Periode 2014 – 2018) - Karmila Indah Pratiwi; Ade Ali Nurdin; Tjetjep Djuwarsa (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This research aims to measure the level of financial health of PT. Jasa Marga (Persero) Tbk. 2014 - 2018 period based on SK. Minister of BUMN No. KEP-100 / MBU / 2002 and this research focuses on one aspect, namely the financial aspect. This research uses 8 analysis aspect, namely ROE, ROI, Cash Ratio, Current Ratio, Collection Periods, InventoryxTurnover (ITO), TotalsAsset Turnover (TATO), and TMS againstwTA. This research method using descriptive method. The type of data used is quantitative data. The data source used is secondary data obtained from financial reports through www.jasamarga.com. Based on the results of the analysis that has been done, the level of financial health of PT. Jasa Marga (Persero) Tbk in 2014 received the predicate A (Healthy). In 2015 received the predicatewA (Healthy). In 2016 received the predicate BBB (Less Healthy). Inz2017 received the predicate BBB (Less Healthy). In 2018 received thewpredicate BBB (Less Healthy).